Dexmedetomidine disrupts esophagus cancer tumorigenesis by modulating circ_0003340/miR-198/HMGA2 axis. Issue 5 (23rd March 2022) - Che, Jianpeng; Liu, Mingming; Lv, Hongwei
Abstract : More and more studies have focused on the regulatory role of circular RNAs (circRNAs) in various cancers. However, it is not clear how dexmedetomidine (DEX) affects esophagus cancer progression by affecting the expression of circRNAs. This study aimed to investigate the role of DEX in esophagus cancer and its underlying mechanism. Cell Counting Kit-8 assay and 5-ethynyl-2′-deoxyuridine assays were conducted to evaluate cell proliferation. Flow cytometry analysis and transwell assay were performed for cell apoptosis and invasion. The protein levels of cleaved caspase-3, matrix metallopeptidase 9, and high mobility group AT-hook 2 (HMGA2) were assessed by western blot assay. The expression levels of circ_0003340 and microRNA-198 (miR-198) were determined by quantitative real-time PCR. Dual-luciferase reporter assay was performed to verify the interaction between miR-198 and circ_0003340 or HMGA2. Murine xenograft model was established to investigate the role of circ_0003340 and DEX in vivo . DEX exerted antitumor effects in esophagus cancer cells. DEX hindered proliferation and invasion while inducing apoptosis of esophagus cancer cells, which was abolished by circ_0003340 elevation, HMGA2 overexpression, or miR-198 silencing. miR-198 directly interacted with circ_0003340 and HMGA2 in esophagus cancer cells. Moreover, knockdown of circ_0003340 could improve the anticancer role of DEX in vivo . DEX constrained cell carcinogenesis by regulating circ_0003340/miR-198/HMGA2 axis in esophagus cancer, providing an effective clinical implication for preventing the development of the esophagus cancer by the DEX.